Eco-Teology: Implementasi Kelompok Sunda Wiwitan Dalam Mempertahankan Ekosistem - Adil, Muhammad adil muttaqin; , Sabrina Trias Safithry; Maretha Nur Safira Ainaya; Vania Bintang Aurora; Ikmal Ardiansyah5; Aditia Muhammad Noor (At-Tuhfah : Jurnal Studi Keislaman, 2025)
Ecotheology is the study that refers to the relationship between God, the Creator, and organisms in the terrain. Sunda Wiwitan is a former Sundanese belief system and its training came from the elders who empowered their successors to continue the religion. When you hear the word" Sundanese", some people presumably suppose that the Sundanese are the dominant lineage in West Java. Or, more generally, Sundanese are the occupants of West Java. Ecosystems that begin to be defiled with chemicals, mortal conditioning that don't admire the rights of nature can grow and develop duly without restrictions on the use of natural resource products. Sundanese wiwitan as an ancient tutoring has quite an important part for the ecosystem in the girding terrain because in its training applying customary or pikukuh rules it has the sound lojor teu meunang being cut, pondok teu meunang being spliced which means long can not be cut, short can not be joined. This composition aims to understand and dissect Sunda Wiwitan as votaries of beliefs and the part they play in maintaining the ecosystem. There are two benefits in this composition, including theoretical and practical benefits. The theoretical benefits of this composition are to introduce the Sunda Wiwitan religion to the public. The exploration system used is descriptive system through a qualitative approach in the form of rulings or statements. The type of exploration used is descriptive exploration. Data collection through literature and literature exploration aims to include clear and detailed being information supported by colorful sources of exploration conducted through journals or scientific papers.